Organic versus conventional fertilization effects on sweet basil (Ocimum basilicum L.) growth in a greenhouse system - Bufalo, Jennifer [UNESP]; Cantrell, Charles L.; Astatkie, Tessema; Zheljazkov, Valtcho D.; Gawde, Archana; Boaro, Carmen Sílvia Fernandes [UNESP] (Elsevier, 2015)
Ocimum basilicum L. (sweet basil) is an essential oil producing crop used in culinary and fragrance applications. The objective of this controlled environment study was to evaluate the effects of organic and conventional fertilization (applied at two nitrogen rates, 150 and 250 kg N/ha) on plant growth, essential oil yield and chemical profile, and tissue nutrient accumulation in sweet basil. Overall, basil plants fertilized with organic fertilizer at a rate of 150 kg N/ha accumulated greater concentrations of potassium (K) and manganese (Mn). The highest fresh weight was obtained from the plants grown with conventional fertilizer at a rate of 250. kg N/ha Treatments did not affect the oil content in dried biomass (0.23-0.36% range), oil yields (11.4-20.7 mg/pot), nor the concentration of eucalyptol, (-)-linalool, bornyl acetate, eugenol, α-trans-bergamotene, germacrene D, γ{baby}-cadinene and epi-α-cadinol in basil oil. The results from this study demonstrated that organic or conventional fertilizer can alter fresh or dry weight, and nutrient absorption without modifying essential oil composition.
Keywords: (-)-Linalool; Essential oil; Eugenol; Nitrogen; Nutrients